The health benefits of attaining and strengthening air quality standards in Cape Town - Keen, S.; Altieri, K. (Clean Air Journal, 2016)
The link between pollution and poor health and mortality has been established globally. Developing countries carry most of the burden of ill health from air pollution, and urban centres like the City of Cape Town even more so. Effective air quality management to protect human health relies on the attainment of air quality standards. This study uses the Benefits Mapping and Analysis Program (BenMAP) along with a locally derived exposure-response function and air quality monitor data to investigate whether the consistent attainment of current or more stringent air quality standards would avoid loss of life. The results show that attaining the PM10 24-hour mean South Africa National Standard limit and the PM10 and SO2 24-hour mean World Health Organisation guidelines in Cape Town reduces levels of pollutants and does reduce excess risk of mortality in Cape Town.